Strategies for Developing and Implementing Digital Business in Online Marketing for MSMEs in Semarang Regency - Teguh Setiadi; Priyadi Priyadi; Robby Andika Kusumajaya; Susanti Dwi Ilhami (Jurnal Pengabdian Masyarakat Al-Fatimah, 2024)
Small and Medium Enterprises (SMEs) play a vital role in the global business landscape, contributing significantly to economic growth and employment. In the era of digital transformation, digital marketing has become increasingly important for enhancing the performance of SMEs. In today’s dynamic business environment, leveraging digital marketing strategies empowers these enterprises to thrive and overcome challenges in the digital era, thereby driving growth and sustainability. This study explores and synthesizes existing literature to assess the impact of digital marketing on SME performance. The findings reveal a consistent and significant pattern: digital marketing has a positive influence on the sales performance of SMEs in the Semarang Regency area. By adopting digital marketing, SMEs benefit from increased market reach, enhanced customer engagement, greater brand visibility, and improved competitive advantage. Digital marketing has emerged as a powerful tool for strengthening the competitiveness and success of SMEs in the digital age